A Effect of Different Pipe Diameters to The Flow Behaviour of The Pipeline in UTHM Biodiesel - Pelias Pog, Stefina Edora; Abd Rashid, Razlin; Mohd Salleh, Zuliazura; Mat Hassan, Nik Normunira; Hussin, Rosniza (Progress in Engineering Application and Technology, 2020)
Pipelines transport flammable or explosive materials, such as natural gas or oil raise specific safety concerns and have encountered various incidents. The aim of this study is to determine the effect of the pipeline’s size on the flow behavior and to identify the pipe diameter suitable for fluid properties of B100 in the UTHM Biodiesel Pilot Plant. The study was conducted with three different pipe sizes of its inlet diameter named, Geometry 1 with 120 mm, Geometry 2 with 180 mm and Geometry 3 with 290 mm. There are three types of inlet velocity used which is Velocity 1 with 0.98 m/s, Velocity 2 with 1.1 m/s and Velocity 3 with 1.15 m/s. Geometry 2 and Velocity 2 are the actual parameter of the pipeline in this study. The study was conducted based on UTHM Biodiesel Pilot Plant which focuses on the trans-esterification inlet process. This study was used B100 fluid properties as a raw material in the pipe. The simulation procedure was performed in a structured grid by using ANSYS. Pressure and velocity measurements are made for three types of pipelines. Pressure and velocity are also theoretically studied using 3D-CFD analysis to show the flow behavior of three geometry types and three different inlet velocity values. High velocity value can cause noise, vibration, and higher stress. Geometry 1 achieved a good flow behavior when Velocity 1 was applied. Selecting Velocity 2 for Geometry 2 is recommended. Velocity 3 are suitable for Geometry 3 because of the pipeline size. Overall a good flow behavior in the pipeline will improve the efficiency of pipeline and its lifespan.